PENGEMBANGAN VIDEO STOP MOTION MUSIK ANSAMBEL PENTATONIS PADA MATA PELAJARAN SBdP UNTUK SISWA SEKOLAH DASAR - Andika Gutama; Cicilia Ika Rahayu Nita; Rurin Listiani (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
Abstract Learning activities at SDN Watesnegoro 1, Mojokerto Regency during the COVID-19 pandemic were carried out in a blended learning manner. In these learning activities the teacher still uses teaching materials in printed form. Based on the problems found, the researchers developed a music stop motion video for the pentatonic ensemble for class V SBdP subjects at SDN Watesnegoro 1, Mojokerto Regency which aims to determine the process of developing, feasibility, practical, and effective stop motion video learning media. The research used is a 4D model consisting of definition, design, development and dissemination. The data used in this study are qualitative and quantitative data. This study uses 2 stages of trials, namely broad trials and limited trials. The results of this product development trial, namely a stop motion video for pentatonic ensemble music, were declared very feasible with the percentage of material experts 90%, media experts 92.5% and linguists 92.5%. The stop motion video was stated to be very practical based on the teacher's response questionnaire which obtained a percentage of 82% and a limited trial assessment of 10 students who obtained a percentage of 88.5% and a broad trial of 20 students obtained a percentage of 92%. At the stage of testing the effectiveness of the stop motion video, it is stated that it is very effective. This research is expected to be useful and become a reference for other researchers in developing interesting and fun learning videos for students. Keywords: Pentatonic Ensemble Music, Stop Motion Video, SBdP